A radiation refrigeration masterbatch for continuous refrigeration and preparation method thereof

By developing radiated refrigeration maternal particles containing fluoride modified aluminum phosphate, modified silicide, and modified hybrid cellulose, the problem of poor refrigeration effect and low efficiency of existing refrigeration materials, achieve better refrigeration effects and better refrigeration effects and The duration is suitable for market demand.

CN118791881BActive Publication Date: 2025-01-28SUZHOU ZHONGCUI NANO NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410847179.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-01-28
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

The existing refrigeration materials have poor refrigeration efficiency, low refrigeration efficiency, greatly reduced the refrigeration effect over time, and have high cost, which limits their application.

Method used

Develop a radiation -refrigerated parent particle containing fluoride modified aluminum phosphate, modified silicide, and modified hybrid cellulose. It improves its cooling and refrigeration performance through the combination and processing of modified materials.

Benefits of technology

A better radiation refrigeration effect is achieved, the duration of cooling is longer, suitable for market demand, and at the same time give anti -corrosion effects and extend the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005177126870000101
    Figure GDA0005177126870000101
  • Figure GDA0005177126870000111
    Figure GDA0005177126870000111
Patent Text Reader

Abstract

The present invention relates to the technical field of refrigeration materials, and discloses a radiation refrigeration masterbatch for continuous refrigeration and a preparation method thereof, comprising fluorine-modified aluminum phosphate, modified siloxane, and modified mixed cellulose. Aluminum phosphate is fluorine-modified, siloxane is end-hydroxylated, connected with methylamine and ethylamine by hydrogen bonds, wood cellulose and bacterial cellulose are melt-modified with L-lactide, and 8-hydroxyquinoline is blended and modified. Methylamine and ethylamine are connected by hydrogen bonds without destroying their refrigeration effect, and form a synergistic refrigeration effect with siloxane. Wood cellulose and bacterial cellulose have a good refrigeration effect. After modification, their strength is greatly improved, and the refrigeration and cooling effect is greatly improved. At the same time, an antiseptic effect is given to extend the service life. This product has a good radiation refrigeration effect, and due to its material properties, the duration of cooling is also better, which is more suitable for market demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refrigeration materials, and in particular to a radiation refrigeration masterbatch for continuous refrigeration and a preparation method thereof. Background Art

[0002] Radiative cooling is a passive cooling technology that radiates heat directly to the outside world. It does not require additional energy input and can effectively reduce energy loss, which is of great significance to energy issues. However, many current refrigeration materials have poor cooling effects and low cooling efficiency. As time goes by, the cooling effect will be greatly reduced, which will cause many problems in actual use. At the same time, the cost of achieving a good cooling effect will also increase greatly, which will be limited in application. Therefore, it is necessary to develop a radiative cooling material that can continuously cool, simplify the process, reduce costs, and meet market demand. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the deficiencies in the prior art, the present invention provides a radiation refrigeration masterbatch for continuous refrigeration and a preparation method thereof, which has a better refrigeration effect.

[0005] (II) Technical solution

[0006] A radiation refrigeration masterbatch for continuous refrigeration comprises the following weight components:

[0007] 10-20 parts of fluorine-modified aluminum phosphate, 20-30 parts of modified siloxane, 40-60 parts of modified mixed cellulose;

[0008] The preparation method of the radiation refrigeration masterbatch is as follows:

[0009] (1) adding sodium aluminate to hot water and stirring evenly, heating to 80-90° C., adding 60-80% by mass of phosphoric acid, controlling the pH value to 4.0-4.5, transferring the reaction product to an autoclave, heating at 200-300° C. for 10-30 hours, centrifuging, washing with dilute hydrochloric acid and water, and drying to obtain aluminum phosphate; adding aluminum phosphate, sodium fluoride, and cyclohexylamine to water, stirring evenly, reacting at 150-300° C. for 20-30 hours, and removing the solvent by reduced pressure distillation to obtain fluorine-modified aluminum phosphate;

[0010] (2) octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, hydroxy silicone oil, and catalyst tetramethylammonium hydroxide are mixed, vacuum dehydrated at 50-60° C. for 30-60 min, introduced with dry nitrogen, heated to 80-90° C. for reaction for 1-4 h, heated to 110-120° C. for reaction for 2-6 h, then heated to 150-180° C. for 20-60 min, and vacuumed to obtain hydroxy-terminated polydimethylsiloxane;

[0011] (3) adding methylamine and ethylamine to the ethanol solution, stirring evenly to prepare an amine solution, heating the terminal hydroxyl polydimethylsiloxane to 50-65° C., adding the amine solution and initiator ammonium persulfate, heating to 80-100° C., reacting for 2-6 hours, and removing the solvent by reduced pressure distillation to obtain amine-modified terminal hydroxyl polydimethylsiloxane, i.e., modified siloxane;

[0012] (4) placing biomass sawdust into a de-lignified solution, heating to boiling and stirring for 3 to 6 hours, removing the lower layer of wood cellulose, washing it with deionized water, and then immersing it in a boiling bleaching solution until the wood cellulose turns white, taking it out and washing it with deionized water for 2 to 5 times to obtain a wood cellulose dispersion; using a basic culture medium to culture black tea fungi, statically culturing it at 28 to 36°C for 7 to 14 days, after the cultivation is completed, a cellulose film floats on the surface, taking it out and washing it with deionized water, then immersing it in a 0.1 mol / L sodium hydroxide solution, boiling it for 20 to 40 minutes, and placing it in physiological saline at 121°C for high temperature sterilization for 20 minutes to obtain bacterial cellulose; mixing the wood cellulose dispersion and the bacterial cellulose and stirring them evenly, removing the solvent by reduced pressure distillation to obtain a mixed cellulose;

[0013] (5) Mixing the mixed cellulose, L-lactide and stannous octoate, evacuating the mixture, stirring continuously, reacting at 80-90° C. for 30-60 min, heating to 130-150° C., continuing the reaction for 10-20 h, then mixing with 8-hydroxyquinoline, adding to an ethanol solution, stirring evenly, and removing the solvent by distillation under reduced pressure to obtain a modified mixed cellulose;

[0014] (6) The fluorine-modified aluminum phosphate, the modified siloxane, and the modified mixed cellulose are mixed, stirred evenly, extruded through a single-screw extruder, water-cooled, pulled, pelletized, and dried to obtain a radiation refrigeration masterbatch.

[0015] Preferably, in the step (1), the mass ratio of sodium aluminate to phosphoric acid is 1:2-4; the mass ratio of aluminum phosphate to sodium fluoride to cyclohexylamine is 1:0.05-0.2:10-15.

[0016] Preferably, in step (2), the mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, hydroxy silicone oil and catalyst tetramethylammonium hydroxide is 1:0.01-0.03:0.1-0.3:0.03-0.08.

[0017] Preferably, in step (3), the mass ratio of methylamine, ethylamine, terminal hydroxyl polydimethylsiloxane, and initiator ammonium persulfate is 1:0.8-1.2:2-3.5:0.05-0.08.

[0018] Preferably, the delignified solution in step (4) is a mixed solution of sodium hydroxide, solid sodium sulfite and deionized water in a mass ratio of 1:1 to 3:10 to 20.

[0019] Preferably, the basal culture medium in step (4) is 20-25 g / L mannitol, 3-5 g / L tryptone, 2-6 g / L glucose, 20-30 g / L agar, pH 5.0, and sterilized at 121°C for 20 min.

[0020] Preferably, in step (4), the mass ratio of the wood cellulose dispersion to the bacterial cellulose is 1:0.2-0.4.

[0021] Preferably, in step (5), the mass ratio of the mixed cellulose, L-lactide, stannous octoate and 8-hydroxyquinoline is 1:1.5-2:0.05-0.2:0.5-0.8.

[0022] (III) Beneficial technical effects

[0023] A radiation refrigeration masterbatch for continuous refrigeration comprises fluorine-modified aluminum phosphate, modified siloxane and modified mixed cellulose.

[0024] Aluminum phosphate is modified with fluorine, siloxane is terminally hydroxylated, connected with methylamine and ethylamine by hydrogen bonds, wood cellulose and bacterial cellulose are melt-modified with L-lactide, and 8-hydroxyquinoline is blended and modified. After modification, the cooling performance can be effectively improved. Methylamine and ethylamine are commonly used refrigerants. They are connected by hydrogen bonds without destroying their cooling effect, and form a synergistic cooling effect with siloxane. Wood cellulose has a good radiation cooling effect, and bacterial cellulose also has a good cooling effect. After modification, its strength is greatly improved, and the cooling effect is greatly improved. At the same time, it has an anti-corrosion effect and extends its service life.

[0025] This product has a good radiation cooling effect, and due to its material properties, the cooling duration is also better, which is more suitable for market demand. DETAILED DESCRIPTION

[0026] Example 1

[0027] (1) Add 10 g of sodium aluminate to 60 mL of hot water and stir evenly, heat to 80° C., add 20 g of 60% by mass phosphoric acid, control the pH to 4.0, transfer the reaction product to an autoclave, heat at 200° C. for 10 h, centrifuge, wash with dilute hydrochloric acid and water, and dry to obtain aluminum phosphate; add 10 g of aluminum phosphate, 1.5 g of sodium fluoride, and 100 mL of cyclohexylamine to 500 mL of water, stir evenly, react at 150° C. for 20 h, and remove the solvent by reduced pressure distillation to obtain fluorine-modified aluminum phosphate.

[0028] (2) 20 g of octamethylcyclotetrasiloxane, 0.2 g of tetramethyltetravinylcyclotetrasiloxane, 5 mL of hydroxy silicone oil, and 0.6 g of tetramethylammonium hydroxide catalyst were mixed, vacuum dehydrated at 50° C. for 30 min, introduced with dry nitrogen, heated to 80° C. for reaction for 1 h, heated to 110° C. for reaction for 2 h, and then heated to 150° C. for 20 min, and evacuated to obtain terminal hydroxyl polydimethylsiloxane.

[0029] (3) 10 g of methylamine and 8 g of ethylamine are added to an ethanol solution and stirred to prepare an amine solution. The terminal hydroxyl polydimethylsiloxane is heated to 50° C., the amine solution and 0.5 g of initiator ammonium persulfate are added, the temperature is raised to 80° C., the reaction is carried out for 2 h, and the solvent is removed by distillation under reduced pressure to obtain amine-modified terminal hydroxyl polydimethylsiloxane, i.e., modified siloxane.

[0030] (4) 80 g of biomass sawdust was placed in 500 mL of de-lignification solution, heated to boiling and stirred for 3 h, the lower layer of wood cellulose was removed, washed with deionized water, and then immersed in a boiling bleaching solution until the wood cellulose turned white, and then removed and washed twice with deionized water to obtain a wood cellulose dispersion; the black tea fungus was cultured using a basic culture medium and cultured at 28 °C for 7 days. After the culture was completed, a cellulose film floated on the surface, which was removed and washed with deionized water, then immersed in a 0.1 mol / L sodium hydroxide solution, boiled for 20 min, and placed in physiological saline at 121 °C for high temperature sterilization for 20 min to obtain bacterial cellulose; 50 g of the wood cellulose dispersion was mixed with 10 g of bacterial cellulose and stirred evenly, and the solvent was removed by vacuum distillation to obtain a mixed cellulose.

[0031] The delignification solution is a mixed solution of sodium hydroxide, solid sodium sulfite and deionized water in a mass ratio of 1:1:10.

[0032] The basic culture medium is composed of 20 g / L mannitol, 3 g / L tryptone, 2 g / L glucose, and 20 g / L agar, with a pH of 5.0 and sterilized at 121° C. for 20 min.

[0033] (5) Mix the mixed cellulose, 90 g of L-lactide and 3 g of stannous octoate, evacuate the mixture, stir continuously, react at 80° C. for 30 min, raise the temperature to 130° C. and continue to react for 10 h. Then, mix the mixture with 30 g of 8-hydroxyquinoline, add the mixture to an ethanol solution, stir evenly, and remove the solvent by distillation under reduced pressure to obtain a modified mixed cellulose.

[0034] (6) 10 g of fluorine-modified aluminum phosphate, 20 g of modified siloxane, and 40 g of modified mixed cellulose were mixed, stirred evenly, extruded through a single-screw extruder, water-cooled, pulled, pelletized, and dried to obtain a radiation refrigeration masterbatch.

[0035] Example 2

[0036] (1) 20 g of sodium aluminate is added to 120 mL of hot water and stirred evenly, heated to 90° C., 80 g of 80% phosphoric acid is added, the pH is controlled to 4.5, and the reaction product is transferred to an autoclave, heated at 300° C. for 30 h, centrifuged, washed with dilute hydrochloric acid and water, and dried to obtain aluminum phosphate; 30 g of aluminum phosphate, 6 g of sodium fluoride, and 450 mL of cyclohexylamine are added to 1200 mL of water, stirred evenly, reacted at 300° C. for 30 h, and the solvent was removed by reduced pressure distillation to obtain fluorine-modified aluminum phosphate.

[0037] (2) 40 g of octamethylcyclotetrasiloxane, 1.2 g of tetramethyltetravinylcyclotetrasiloxane, 15 mL of hydroxy silicone oil, and 3.2 g of tetramethylammonium hydroxide catalyst were mixed, vacuum dehydrated at 60° C. for 60 min, introduced with dry nitrogen, heated to 90° C. for reaction for 4 h, heated to 120° C. for reaction for 6 h, then heated to 180° C. for 60 min, and evacuated to obtain terminal hydroxyl polydimethylsiloxane.

[0038] (3) 20 g of methylamine and 24 g of ethylamine are added to an ethanol solution and stirred to prepare an amine solution. The terminal hydroxyl polydimethylsiloxane is heated to 65° C., the amine solution and 1.6 g of initiator ammonium persulfate are added, the temperature is raised to 100° C., the reaction is carried out for 6 hours, and the solvent is removed by distillation under reduced pressure to obtain amine-modified terminal hydroxyl polydimethylsiloxane, i.e., modified siloxane.

[0039] (4) 150 g of biomass sawdust was placed in 1200 mL of de-lignification solution, heated to boiling and stirred for 6 h, the lower layer of wood cellulose was removed, washed with deionized water, and then immersed in a boiling bleaching solution until the wood cellulose turned white, and then removed and washed with deionized water for 5 times to obtain a wood cellulose dispersion; the black tea strain was cultured using a basic culture medium and cultured at 36 °C for 14 days. After the culture was completed, a cellulose film floated on the surface, which was removed and washed with deionized water, then immersed in a 0.1 mol / L sodium hydroxide solution, boiled for 40 min, and placed in physiological saline at 121 °C for high temperature sterilization for 20 min to obtain bacterial cellulose; 80 g of the wood cellulose dispersion was mixed with 32 g of bacterial cellulose and stirred evenly, and the solvent was removed by vacuum distillation to obtain a mixed cellulose.

[0040] The delignification solution is a mixed solution of sodium hydroxide, solid sodium sulfite and deionized water in a mass ratio of 1:3:20.

[0041] The basic culture medium is composed of 25 g / L mannitol, 5 g / L tryptone, 6 g / L glucose, 30 g / L agar, pH 5.0, and sterilized at 121° C. for 20 min.

[0042] (5) Mix the mixed cellulose, 160 g of L-lactide and 16 g of stannous octoate, evacuate the mixture, stir continuously, react at 90° C. for 60 min, raise the temperature to 150° C. and continue to react for 20 h. Then, mix the mixture with 64 g of 8-hydroxyquinoline, add the mixture to an ethanol solution, stir evenly, and remove the solvent by distillation under reduced pressure to obtain a modified mixed cellulose.

[0043] (6) 20 g of fluorine-modified aluminum phosphate, 30 g of modified siloxane, and 60 g of modified mixed cellulose were mixed and stirred evenly, extruded through a single-screw extruder, water-cooled, pulled, pelletized, and dried to obtain a radiation refrigeration masterbatch.

[0044] Example 3

[0045] (1) 12 g of sodium aluminate is added to 80 mL of hot water and stirred evenly, heated to 90° C., 40 g of 70% by mass phosphoric acid is added, the pH is controlled to 4.5, and the reaction product is transferred to an autoclave, heated at 240° C. for 20 h, centrifuged, washed with dilute hydrochloric acid and water, and dried to obtain aluminum phosphate; 15 g of aluminum phosphate, 2 g of sodium fluoride, and 200 mL of cyclohexylamine are added to 600 mL of water, stirred evenly, reacted at 180° C. for 25 h, and the solvent is removed by reduced pressure distillation to obtain fluorine-modified aluminum phosphate.

[0046] (2) 25 g of octamethylcyclotetrasiloxane, 0.5 g of tetramethyltetravinylcyclotetrasiloxane, 10 mL of hydroxy silicone oil, and 1 g of catalyst tetramethylammonium hydroxide were mixed, vacuum dehydrated at 55° C. for 40 min, introduced dry nitrogen, heated to 90° C. for reaction for 2 h, heated to 120° C. for reaction for 5 h, and then heated to 160° C. for 40 min, and evacuated to obtain terminal hydroxyl polydimethylsiloxane.

[0047] (3) 15 g of methylamine and 10 g of ethylamine are added to the ethanol solution and stirred to prepare an amine solution. The terminal hydroxyl polydimethylsiloxane is heated to 55° C., the amine solution and 0.8 g of initiator ammonium persulfate are added, the temperature is raised to 100° C., the reaction is carried out for 4 hours, and the solvent is removed by distillation under reduced pressure to obtain amine-modified terminal hydroxyl polydimethylsiloxane, i.e., modified siloxane.

[0048] (4) 100 g of biomass sawdust was placed in 800 mL of de-lignification solution, heated to boiling and stirred for 5 h, the lower layer of wood cellulose was removed, washed with deionized water, and then immersed in a boiling bleaching solution until the wood cellulose turned white, and then removed and washed with deionized water for 4 times to obtain a wood cellulose dispersion; the black tea fungus was cultured using a basic culture medium and cultured at 30 °C for 10 days. After the culture was completed, a cellulose film floated on the surface, which was removed and washed with deionized water, then immersed in a 0.1 mol / L sodium hydroxide solution, boiled for 25 min, and placed in physiological saline at 121 °C for high temperature sterilization for 20 min to obtain bacterial cellulose; 60 g of the wood cellulose dispersion was mixed with 15 g of bacterial cellulose and stirred evenly, and the solvent was removed by reduced pressure distillation to obtain a mixed cellulose.

[0049] The delignification solution is a mixed solution of sodium hydroxide, solid sodium sulfite and deionized water in a mass ratio of 1:2:15.

[0050] The basic culture medium is composed of 25 g / L mannitol, 3 g / L tryptone, 2 g / L glucose, 30 g / L agar, pH 5.0, and sterilized at 121° C. for 20 min.

[0051] (5) Mix the mixed cellulose, 100 g of L-lactide, and 5 g of stannous octoate, evacuate the mixture, stir continuously, react at 90° C. for 40 min, raise the temperature to 140° C., continue to react for 15 h, then mix with 40 g of 8-hydroxyquinoline, add to an ethanol solution, stir evenly, and remove the solvent by distillation under reduced pressure to obtain a modified mixed cellulose.

[0052] (6) 15 g of fluorine-modified aluminum phosphate, 26 g of modified siloxane, and 48 g of modified mixed cellulose were mixed and stirred evenly, extruded through a single-screw extruder, water-cooled, pulled, pelletized, and dried to obtain a radiation refrigeration masterbatch.

[0053] Example 4

[0054] (1) 15 g of sodium aluminate is added to 100 mL of hot water and stirred evenly, heated to 90° C., 50 g of 80% by mass phosphoric acid is added, the pH is controlled to 4.0, and the reaction product is transferred to an autoclave, heated at 250° C. for 20 h, centrifuged, washed with dilute hydrochloric acid and water, and dried to obtain aluminum phosphate; 20 g of aluminum phosphate, 3 g of sodium fluoride, and 200 mL of cyclohexylamine are added to 900 mL of water, stirred evenly, reacted at 200° C. for 30 h, and the solvent was removed by reduced pressure distillation to obtain fluorine-modified aluminum phosphate.

[0055] (2) 30 g of octamethylcyclotetrasiloxane, 0.8 g of tetramethyltetravinylcyclotetrasiloxane, 10 mL of hydroxy silicone oil, and 2 g of tetramethylammonium hydroxide catalyst were mixed, vacuum dehydrated at 60° C. for 60 min, introduced dry nitrogen, heated to 80° C. for reaction for 1 h, heated to 110° C. for reaction for 2 h, and then heated to 180° C. for 50 min, and evacuated to obtain terminal hydroxyl polydimethylsiloxane.

[0056] (3) 18 g of methylamine and 20 g of ethylamine are added to the ethanol solution and stirred to prepare an amine solution. The terminal hydroxyl polydimethylsiloxane is heated to 60° C., the amine solution and 1.2 g of initiator ammonium persulfate are added, the temperature is raised to 100° C., the reaction is carried out for 5 h, and the solvent is removed by distillation under reduced pressure to obtain amine-modified terminal hydroxyl polydimethylsiloxane, i.e., modified siloxane.

[0057] (4) 120 g of biomass sawdust was placed in 1000 mL of de-lignification solution, heated to boiling and stirred for 5 h, the lower layer of wood cellulose was removed, washed with deionized water, and then immersed in a boiling bleaching solution until the wood cellulose turned white, and then removed and washed with deionized water for 4 times to obtain a wood cellulose dispersion; the black tea strain was cultured using a basic culture medium and cultured at 32 °C for 7 days. After the culture was completed, a cellulose film floated on the surface, which was removed and washed with deionized water, then immersed in a 0.1 mol / L sodium hydroxide solution, boiled for 30 min, and placed in physiological saline at 121 °C for high temperature sterilization for 20 min to obtain bacterial cellulose; 70 g of the wood cellulose dispersion was mixed with 25 g of bacterial cellulose and stirred evenly, and the solvent was removed by vacuum distillation to obtain a mixed cellulose.

[0058] The delignification solution is a mixed solution of sodium hydroxide, solid sodium sulfite and deionized water in a mass ratio of 1:3:20.

[0059] The basic culture medium is composed of 20 g / L mannitol, 5 g / L tryptone, 6 g / L glucose, 30 g / L agar, pH 5.0, and sterilized at 121° C. for 20 min.

[0060] (5) Mix the mixed cellulose, 120 g of L-lactide and 12 g of stannous octoate, evacuate the mixture, stir continuously, react at 80° C. for 50 min, raise the temperature to 150° C. and continue to react for 20 h. Then, mix the mixture with 50 g of 8-hydroxyquinoline, add the mixture to an ethanol solution, stir evenly, and remove the solvent by distillation under reduced pressure to obtain a modified mixed cellulose.

[0061] (6) 18 g of fluorine-modified aluminum phosphate, 26 g of modified siloxane, and 50 g of modified mixed cellulose were mixed and stirred evenly, extruded through a single-screw extruder, water-cooled, pulled, pelletized, and dried to obtain a radiation refrigeration masterbatch.

[0062] Example 5

[0063] (1) Add 20 g of sodium aluminate to 100 mL of hot water, stir evenly, heat to 90° C., add 60 g of 60% phosphoric acid, control the pH to 4.5, transfer the reaction product to an autoclave, heat at 280° C. for 20 h, centrifuge, wash with dilute hydrochloric acid and water, and dry to obtain aluminum phosphate; add 20 g of aluminum phosphate, 5 g of sodium fluoride, and 400 mL of cyclohexylamine to 1000 mL of water, stir evenly, react at 200° C. for 30 h, and remove the solvent by reduced pressure distillation to obtain fluorine-modified aluminum phosphate.

[0064] (2) 30 g of octamethylcyclotetrasiloxane, 1 g of tetramethyltetravinylcyclotetrasiloxane, 12 mL of hydroxy silicone oil, and 3 g of catalyst tetramethylammonium hydroxide were mixed, vacuum dehydrated at 60° C. for 30 min, introduced dry nitrogen, heated to 90° C. for reaction for 1 h, heated to 120° C. for reaction for 6 h, and then heated to 160° C. for 50 min, and evacuated to obtain terminal hydroxyl polydimethylsiloxane.

[0065] (3) 20 g of methylamine and 8 g of ethylamine are added to an ethanol solution and stirred to prepare an amine solution. The terminal hydroxyl polydimethylsiloxane is heated to 60° C., the amine solution and 1.5 g of initiator ammonium persulfate are added, the temperature is raised to 90° C., the reaction is carried out for 5 h, and the solvent is removed by distillation under reduced pressure to obtain amine-modified terminal hydroxyl polydimethylsiloxane, i.e., modified siloxane.

[0066] (4) 140 g of biomass sawdust was placed in 1000 mL of de-lignification solution, heated to boiling and stirred for 5 h, the lower layer of wood cellulose was removed, washed with deionized water, and then immersed in a boiling bleaching solution until the wood cellulose turned white, and then removed and washed with deionized water for 4 times to obtain a wood cellulose dispersion; the black tea fungus was cultured using a basic culture medium and cultured at 35 °C for 14 days. After the culture was completed, a cellulose film floated on the surface, which was removed and washed with deionized water, then immersed in a 0.1 mol / L sodium hydroxide solution, boiled for 30 min, and placed in physiological saline at 121 °C for high temperature sterilization for 20 min to obtain bacterial cellulose; 60 g of the wood cellulose dispersion was mixed with 30 g of bacterial cellulose and stirred evenly, and the solvent was removed by vacuum distillation to obtain a mixed cellulose.

[0067] The delignification solution is a mixed solution of sodium hydroxide, solid sodium sulfite and deionized water in a mass ratio of 1:3:10.

[0068] The basic culture medium is 25 g / L mannitol, 5 g / L tryptone, 2 g / L glucose, 20 g / L agar, pH 5.0, and sterilized at 121° C. for 20 min.

[0069] (5) Mix the mixed cellulose, 140 g of L-lactide and 15 g of stannous octoate, evacuate the mixture, stir continuously, react at 90° C. for 60 min, raise the temperature to 150° C. and continue to react for 20 h. Then, mix the mixture with 60 g of 8-hydroxyquinoline, add the mixture to an ethanol solution, stir evenly, and remove the solvent by distillation under reduced pressure to obtain a modified mixed cellulose.

[0070] (6) 20 g of fluorine-modified aluminum phosphate, 20 g of modified siloxane, and 60 g of modified mixed cellulose were mixed, stirred evenly, extruded through a single-screw extruder, water-cooled, pulled, pelletized, and dried to obtain a radiation refrigeration masterbatch.

[0071] Comparative Example 1: Polydimethylsiloxane refrigeration material.

[0072] Performance Test:

[0073] A UV-VIS-NIR spectrometer (integrating sphere) was used to test the reflectivity (solar reflectivity) of the sample to light in the 300-2500nm band.

[0074] The atmospheric window emissivity is tested using a reflectometer, specifically testing the infrared emissivity at a wavelength of 7 to 14 μm (atmospheric window emissivity);

[0075] The daytime radiant cooling power is determined according to the method in ANSI / ASHRAE Standard 138.

[0076] Table 1 Test results

[0077]

[0078] Table 2 Test results after 100 hours

[0079]

[0080] It can be seen from Table 1 that the solar reflectivity, atmospheric window emissivity, and daytime radiation cooling power of Examples 1 to 5 are better than those of Comparative Example 1, and the average temperature difference with the environment is also greater.

[0081] It can be seen from Table 2 that after 100 hours, the difference between the refrigeration effects of Examples 1 to 5 and Comparative Example 1 becomes larger, and the refrigeration effects remain almost unchanged. Examples 1 to 5 have better continuous refrigeration effects.

[0082] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A radiation refrigeration masterbatch for continuous refrigeration, characterized in that: The radiation refrigeration masterbatch comprises the following components by weight: 10-20 parts of fluorine-modified aluminum phosphate, 20-30 parts of modified siloxane, 40-60 parts of modified mixed cellulose; The preparation method of the radiation refrigeration masterbatch is as follows: (1) adding sodium aluminate to hot water and stirring evenly, heating to 80-90° C., adding 60-80% by mass of phosphoric acid, controlling the pH value to 4.0-4.5, transferring the reaction product to an autoclave, heating at 200-300° C. for 10-30 hours, centrifuging, washing with dilute hydrochloric acid and water, and drying to obtain aluminum phosphate; adding aluminum phosphate, sodium fluoride, and cyclohexylamine to water, stirring evenly, reacting at 150-300° C. for 20-30 hours, and removing the solvent by reduced pressure distillation to obtain fluorine-modified aluminum phosphate; (2) octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, hydroxy silicone oil, and catalyst tetramethylammonium hydroxide are mixed, vacuum dehydrated at 50-60° C. for 30-60 min, introduced with dry nitrogen, heated to 80-90° C. for reaction for 1-4 h, heated to 110-120° C. for reaction for 2-6 h, then heated to 150-180° C. for 20-60 min, and vacuumed to obtain hydroxy-terminated polydimethylsiloxane; (3) adding methylamine and ethylamine to the ethanol solution, stirring evenly to prepare an amine solution, heating the terminal hydroxyl polydimethylsiloxane to 50-65° C., adding the amine solution and initiator ammonium persulfate, heating to 80-100° C., reacting for 2-6 hours, and removing the solvent by reduced pressure distillation to obtain amine-modified terminal hydroxyl polydimethylsiloxane, i.e., modified siloxane; (4) placing biomass sawdust into a de-lignified solution, heating to boiling and stirring for 3 to 6 hours, removing the lower layer of wood cellulose, washing it with deionized water, and then immersing it in a boiling bleaching solution until the wood cellulose turns white, taking it out and washing it with deionized water for 2 to 5 times to obtain a wood cellulose dispersion; using a basic culture medium to culture black tea fungi, statically culturing it at 28 to 36°C for 7 to 14 days, after the cultivation is completed, a cellulose film floats on the surface, taking it out and washing it with deionized water, then immersing it in a 0.1 mol / L sodium hydroxide solution, boiling it for 20 to 40 minutes, and placing it in physiological saline at 121°C for high temperature sterilization for 20 minutes to obtain bacterial cellulose; mixing the wood cellulose dispersion and the bacterial cellulose and stirring them evenly, removing the solvent by reduced pressure distillation to obtain a mixed cellulose; (5) Mixing the mixed cellulose, L-lactide and stannous octoate, evacuating the mixture, stirring continuously, reacting at 80-90° C. for 30-60 min, heating to 130-150° C., continuing the reaction for 10-20 h, then mixing with 8-hydroxyquinoline, adding to an ethanol solution, stirring evenly, and removing the solvent by distillation under reduced pressure to obtain a modified mixed cellulose; (6) The fluorine-modified aluminum phosphate, the modified siloxane, and the modified mixed cellulose are mixed, stirred evenly, extruded through a single-screw extruder, water-cooled, pulled, pelletized, and dried to obtain a radiation refrigeration masterbatch.

2. The continuous refrigeration radiation refrigeration masterbatch according to claim 1, characterized in that: In the step (1), the mass ratio of sodium aluminate to phosphoric acid is 1:2-4; the mass ratio of aluminum phosphate, sodium fluoride and cyclohexylamine is 1:0.05-0.2:10-15.

3. The continuous refrigeration radiation refrigeration masterbatch according to claim 1, characterized in that: In the step (2), the mass ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, hydroxy silicone oil and catalyst tetramethylammonium hydroxide is 1:0.01-0.03:0.1-0.3:0.03-0.

08.

4. The continuous refrigeration radiation refrigeration masterbatch according to claim 1, characterized in that: In the step (3), the mass ratio of methylamine, ethylamine, terminal hydroxyl polydimethylsiloxane and initiator ammonium persulfate is 1:0.8-1.2:2-3.5:0.05-0.

08.

5. The continuous refrigeration radiation refrigeration masterbatch according to claim 1, characterized in that: The delignified solution in step (4) is a mixed solution of sodium hydroxide, solid sodium sulfite and deionized water in a mass ratio of 1:1 to 3:10 to 20.

6. The continuous refrigeration radiation refrigeration masterbatch according to claim 1, characterized in that: The basic culture medium in step (4) is 20-25 g / L mannitol, 3-5 g / L tryptone, 2-6 g / L glucose, 20-30 g / L agar, pH 5.0, and sterilized at 121° C. for 20 min.

7. The continuous refrigeration radiation refrigeration masterbatch according to claim 1, characterized in that: In the step (4), the mass ratio of the wood cellulose dispersion to the bacterial cellulose is 1:0.2-0.

4.

8. The continuous refrigeration radiation refrigeration masterbatch according to claim 1, characterized in that: In the step (5), the mass ratio of the mixed cellulose, L-lactide, stannous octoate and 8-hydroxyquinoline is 1:1.5-2:0.05-0.2:0.5-0.8.

Citation Information

Patent Citations

  • Aluminum phosphate uniform powder material for radiation refrigeration and preparation method of aluminum phosphate uniform powder material

    CN110171809A

  • Preparation method of compression-resistant impact-resistant thermal insulation building material

    CN111592281A